The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/cjce.23236
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of macauba kernel oil using supercritical carbon dioxide and compressed propane

Abstract: Macauba kernel oil (MKO) was extracted using supercritical CO 2 and compressed propane as the solvent. The influence of temperature (313-353 K for CO 2 and 303-333 K for propane) and pressure (18-22 MPa for CO 2 and 8-12 MPa for propane) on oil yield was investigated, and the results were compared with conventional extraction. A characterization of oil and defatted meal was performed. Temperature and pressure, in the evaluated range, influenced oil yield with the use of CO 2 . For propane, the oil yield was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 60 publications
(76 reference statements)
1
15
0
Order By: Relevance
“…For all the considered factors, the increase in extraction pressure systematically improved the oil solubility in subcritical fluid. Indeed, the positive effect of pressure on subcritical fluid (n‐butanol) or/and supercritical CO 2 extraction of oil from Nitraria tangutorum (Liu et al ., ), Mucuna (Garcia et al ., ) and macauba kernel oil (Trentini et al ., ) was already reported. However, higher pressure requires higher quality and stability of the equipment, and it also leads to waste energy and increase costs.…”
Section: Resultsmentioning
confidence: 62%
“…For all the considered factors, the increase in extraction pressure systematically improved the oil solubility in subcritical fluid. Indeed, the positive effect of pressure on subcritical fluid (n‐butanol) or/and supercritical CO 2 extraction of oil from Nitraria tangutorum (Liu et al ., ), Mucuna (Garcia et al ., ) and macauba kernel oil (Trentini et al ., ) was already reported. However, higher pressure requires higher quality and stability of the equipment, and it also leads to waste energy and increase costs.…”
Section: Resultsmentioning
confidence: 62%
“…The percentage oil yield decreased with increasing extraction temperature from 75 to 90 °C and then increased with increasing extraction temperature from 90 to 105 °C. This observation occurred from 75 to 90 °C because the solvent density effect might be predominant, leading to the reduction of solvent dissolving ability, and causing a decrease in the oil yield, while the solute vapor pressure is more effective than solvent density resulting in an increase in the oil yield in the range of extraction temperature from 90 to 105 °C (Cuco et al, ; Trentini, Cuco, Cardozo‐Filho, & da Silva, ). Moreover, it was observed that the percentage oil yield increased with increasing extraction time from 5 to 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage oil yield increased with increasing extraction temperature from 75 to 105 °C and increased with increasing extraction time from 5 to 15 min. The increase of extraction temperature using isopropanol increased the vapor pressure of solute, therefore the solubility of solute increased and also the mass transfer of solvent through the tea seed matrix could be enhanced, resulting in an increase of the oil yield in isopropanol solvent (Cuco et al, ; Trentini et al, ). Based on the model above, the optimal conditions for extraction temperature and time were predicted to be 105 °C and 15 min, which gave a maximum oil yield of 15.05%.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing temperature results in an increased mass transfer coefficient and effective diffusivity, but decreased oil solubility. Higher temperature also results in a deceased solvent density and an increased solute vapor pressure (Cuco et al, 2019;Trentini, Cuco, Cardozo-Filho, & Silva, 2018).…”
Section: Crude Oil Yield and Oil Recoverymentioning
confidence: 99%